TOURISM AUGMENTED REALITY APPLICATION (TARA) - MOHAMAD NOOR, MOHAMAD HAFIZ (IRC, 2020)
Industrial 4.0, the revolution of technology is coming influencing all aspect of human life. Augmented reality technology is one of the pillars of industrial 4.0 can give revolution into the world by giving the visual view into the real environment in real time. With this main feature of augmented reality technology will be a great help for human doing especially in planning where they can have better view of outcome of the project before it happen. For example, the constructions of tourist attraction like waterpark with be better with the help of augmented reality technology. Usually, the presentation of the construction project will be in documentation like the expected result image of the project. But with augmented reality, the output of project will be clearer about the specification and architecture structure of the building. By doing this, the inventor and stakeholder of the project will be confident to work on the project due to clear vision of the expected result of the project. This is the reason why this technology needs to fully utilize in all sectors in industry including tourism sector. This technology can help the tourist by gaining new experience in gaining information either when they are travelling or not. In other word is in attractive and interactive ways. By using the mobile based application where the uses continuously grow in all countries, this tourism augmented reality application can help the users to gain information of the tourism place by the mediums of 3 dimensional objects, videos, images, audios and more just by scanning the target images that be set using Android smartphone camera. This technology not just help the tourist to gain knowledges in attractive ways, it also can be one of the ways to promote the country’s tourist attraction places locally and globally at the same time support the development of our country.